Distributed orthogonal space–time block coding in wireless relay networks. Issue 16 (1st November 2013) - Phan, Hoc; Duong, Trung Q.; Zepernick, Hans‐Jürgen; Tsiftsis, Theodoros A.
Abstract : In this study, the authors consider distributed orthogonal space–time block coding for relay‐based channel state information‐assisted amplify‐and‐forward networks. Specifically, they show that opportunistic relaying (OR) is an optimal solution in terms of instantaneous signal‐to‐noise ratio (SNR), that is, it provides the maximum instantaneous SNR under the constraint of fixed transmit power for the relays. In particular, instead of allocating the given transmit power to all relays, letting the best relay transmit with this power is an optimal solution for maximising the received SNR. To exhibit this benefit, Monte Carlo simulations are presented showing superior performance of the OR scheme compared to equal power allocation policy for the considered relay networks. For the considered optimal scenario, the authors further derive analytical expressions for the outage probability and symbol error rate (SER) over quasi‐static independent, not necessarily identically distributed Nakagami‐ m fading channels. They further present asymptotically tight approximations for the outage probability and SER in the high SNR regime, rendering insights into the cooperative diversity behaviour. Finally, numerical results are provided to examine the effect of network parameters on the system performance of the considered network.